PERENCANAAN DAN PELAKSANAAN ANGGARAN DAERAH BERBASIS KINERJA - Abdul Rahman (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Local governments have the authority to regulate and administer their internal affairs based upon the economic principle and task assignment as stated in Law 32/2004 about Local Government as the replacement of Law 22/1999 as well as stated in Law 33/2004 about Fiscal Balance between Central and Local Government as the replacement of Law 25/1999. The local governance administration is financed by local budget within one fiscal year. Law 17/2003 about State Budget, article 19 (1) and (2) state that, in local budget planning, local government agencies as theusers of local budget should design their work plan and budget based on the performance to be achieved. To do this, local government of course needs competent human resources. For this purpose, Board of Finance and Development Control (BPKP) actively assists local governments in designing Performance-Based Local Budgeting